DEVELOPMENT OF COORDINATION ABILITIES OF MIDDLE SCHOOL CHILDREN THROUGH FOOTBALL (Physical Culture and Sport: Scientific Perspective, 2025)
The state of the sphere of physical culture and life of the population at the present stage is a significant challenge for the Ukrainian state. There is a deterioration in the quality of life and health of people, the population is decreasing. In such conditions, motivation and established traditions regarding physical education, a healthy lifestyle, and harmonious physical and mental development of people are lost.The period of children's education in secondary school (grades 5-9) is very important, because at this time the foundations of physical and mental health, necessary skills and abilities for everyday life are formed. The main goal of the subject "Physical Culture" is to form in schoolchildren the motivation to preserve their lives, physical development and the use of physical education tools in organizing their harmonious living space. Children's physical experience is expanded through the acquisition of educational modules. These include swimming, athletics, gymnastics, volleyball, basketball, football, etcFootball can be attributed to those sports in which players are required to have a high level of coordination, because the execution of technical and tactical actions in game situations is constantly changing. The success of the team depends on how confidently and accurately the football player performs technical techniques at a particular moment of the game.Among many sports, football occupies one of the leading places. Its simplicity, accessibility for people of all ages, ease and emotionality of game situations, the need to show will and courage to overcome the actions of the opponent, have made football a popular sport and a valuable means of physical education.In all technical and tactical actions carried out within the framework of competitive activities, the main determining factors of the final result of the game are goals. The individual skills of a player consist of both physical and mental fitness, but the basis of the athleticism of football players is rightfully technical fitness.Playing football allows you to gradually achieve a high level of physical fitness, developing the basic physical qualities of children. To develop the coordination abilities of schoolchildren, we have an arsenal of various tools (static exercises, exercises in motion, exercises with a partner, exercises with an object, etc.).
Keywords: football; middle school children; psychological preparedness; coordination skills